Developing a Self-assessment Model of Risk Management Maturity for Client Organizations of Public Construction Projects: Indonesian Context. (2017) - Wibowo, Andreas; Taufik, Januar
Abstract: This paper presents a self-assessment model to measure the risk management (RM) maturity level of construction public client organizations within the Indonesian context. It used a mixture of Delphi method to select and validate the most relevant attributes and Analytical Hierarchy Process (AHP) to assign the weights of the selected attributes. A total of 34 attributes, categorized under four dimensions (i.e., organizational culture, RM processes, RM resources, and RM implementation) were used. It has been shown that top management commitment, integrity and ethics, and change management capabilities were found to be the most important attribute, suggesting that RM maturity level is more than formal and standardized systems. The RM maturity score was computed by summing the products of AHP-based weights and ratings which were expressed in a 0–3 scale with 0 representing immature and 3 denoting mature level. Given this score, the maturity level of a client organization under evaluation will be classified into one of the following four levels: naive (0–24), novice (25–49), normalized (50–74), and managed (75–100). This model was pilot tested on a governmental unit under the Ministry of Public Works with a satisfactory result.